Solar photovoltaic cable sheath material and tear-resistant photovoltaic cable
By adding enhancers of sodium silicate, ferric chloride and aluminum hydroxide to the photovoltaic cable sheath material, the problem of tear-prone traditional photovoltaic cable sheath material is solved, achieving higher tear resistance and flame retardant properties.
Patent Information
- Application Number
- CN202510100143.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional photovoltaic cable sheath materials are prone to tear under external forces, which affects the integrity of the cable and may cause power transmission failures or safety accidents.
A sheath material consisting of ethylene-propylene rubber, crosslinked polyethylene, zinc oxide, etc. is used, and a reinforcement composed of sodium silicate, ferric chloride and aluminum hydroxide is added to the material to enhance the tear resistance of the material.
It significantly improves the tear resistance of photovoltaic cables, avoids deterioration of cable performance caused by damage, and improves the flame retardant performance of cables in high temperature environments.
Smart Images

Figure CN119529438A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the manufacture of photovoltaic cables, and in particular to a solar photovoltaic cable sheath material and a tear-resistant photovoltaic cable. Background Art
[0002] Against the backdrop of the growing global demand for clean energy, the photovoltaic industry is welcoming unprecedented development opportunities. As a key component of photovoltaic power stations, photovoltaic cables play a vital role in ensuring the stable operation of the system and improving energy conversion efficiency. However, photovoltaic cables are exposed to complex and changeable outdoor environments for a long time. They not only need to withstand the influence of harsh climatic conditions such as high temperature, low temperature, ultraviolet rays, and ozone, but also need to have excellent mechanical strength and flame retardant properties to ensure the safety and stability of power transmission. Although traditional photovoltaic cable sheath materials, such as polyvinyl chloride (PVC) and cross-linked polyethylene (XLPE), meet basic protection needs to a certain extent, their performance still needs to be improved. Traditional cable sheath materials are prone to tearing when subjected to external forces, which not only affects the integrity of the cable, but may also cause power transmission failures and even lead to safety accidents. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a solar photovoltaic cable sheath material; another purpose of the present invention is to provide a tear-resistant photovoltaic cable.
[0004] Technical solution: A solar photovoltaic cable sheath material, comprising the following components by weight: 70-120 parts of ethylene propylene rubber, 10-13 parts of cross-linked polyethylene, 3-7 parts of zinc oxide, 1-4 parts of stearic acid, 1-2 parts of paraffin, 2-5 parts of antioxidant RD, 8-12 parts of zinc borate, 150-200 parts of reinforcing agent, 10-12 parts of high wear-resistant furnace black, 9-13 parts of tricresyl phosphate, 9-13 parts of red phosphorus, 0.5-1 parts of accelerator TMTD, 3-5 parts of DCP, and 1-2 parts of HVA-2.
[0005] Preferably, the composition comprises the following components in parts by weight: 100 parts of ethylene-propylene rubber, 10 parts of cross-linked polyethylene, 5 parts of zinc oxide, 2 parts of stearic acid, 1 part of paraffin, 2 parts of antioxidant RD, 10 parts of zinc borate, 200 parts of reinforcing agent, 10 parts of high wear-resistant furnace black, 10 parts of tricresyl phosphate, 10 parts of red phosphorus, 0.5 parts of accelerator TMTD, 3 parts of DCP and 2 parts of HVA-2.
[0006] Preferably, the enhancer includes sodium silicate, ferric chloride and aluminum hydroxide; the preparation process of the enhancer is: polyvinyl alcohol is melted at 262-267°C to form a polyvinyl alcohol melt, and then aluminum hydroxide is added to the polyvinyl alcohol melt. After mixing evenly, excess polyvinyl alcohol melt on the surface is drained off, and then the mixture of ferric chloride and sodium silicate is evenly mixed with aluminum hydroxide, and then dried at 55-65°C for 10-15 minutes and filtered to obtain the enhancer.
[0007] Preferably, in the mixture of ferric chloride and sodium silicate, the weight ratio of ferric chloride to sodium silicate is 2-4:1-3.
[0008] Preferably, the particle size of aluminum hydroxide is 2-5 mm, and the particle sizes of ferric chloride and sodium silicate are 0.1-0.3 mm; the mixture of ferric chloride and sodium silicate is evenly mixed with aluminum hydroxide and dried, and then filtered through a 200-mesh sieve.
[0009] A tear-resistant cable comprises a conductor, an insulating layer and a sheath layer, wherein the outer side of the conductor is wrapped with the insulating layer, the outer side of the insulating layer is wrapped with the sheath layer, and the sheath layer is made of the above sheath materials; the insulating layer specifically comprises the following components in parts by weight: 70-100 parts of cross-linked polypropylene, 15-20 parts of borax, 8-10 parts of magnesium hydroxide, 3-5 parts of ammonium polyphosphate and 1-3 parts of dicyandiamide.
[0010] Preferably, the preparation process of the insulating layer is: first, the cross-linked polypropylene is melted at 170-176°C to form a cross-linked polypropylene melt, and then borax, magnesium hydroxide, ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0011] Beneficial effects:
[0012] (1) The present invention adds a reinforcing agent consisting of sodium silicate, ferric chloride and aluminum hydroxide to the sheath material. When the sheath material is damaged, the sodium silicate and ferric chloride react under the influence of air moisture to generate colloidal silicic acid carrying ferric hydroxide and aluminum hydroxide and fill the damaged part. At the same time, the aluminum hydroxide can promote the drying of the colloidal silicic acid, thereby repairing the damaged part, thereby avoiding the situation where the tear resistance of the cable is significantly deteriorated due to the damage.
[0013] (2) The present invention not only enables the cable to have good tear resistance and insulation properties, but also good flame retardant properties by adding the insulating layer in the sheath material and the inner layer. When the cable is in a high temperature environment, the borax and magnesium hydroxide in the insulating layer will release crystal water and react with the sodium silicate and ferric chloride in the sheath material to generate colloidal silicic acid carrying ferric hydroxide and aluminum hydroxide and fill the damaged parts caused by high temperature, thereby improving the flame retardant properties of the cable. In combination with ammonium polyphosphate and dicyandiamide, the flame retardant properties of the cable can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a structural schematic diagram of the tear-resistant cable in the present invention. DETAILED DESCRIPTION
[0015] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0016] Example 1 The sheath material includes, by weight, 70 parts of ethylene propylene rubber, 10 parts of cross-linked polyethylene, 3 parts of zinc oxide, 1 part of stearic acid, 1 part of paraffin, 2 parts of antioxidant RD, 8 parts of zinc borate, 150 parts of reinforcing agent, 10 parts of high wear-resistant furnace black, 9 parts of tricresyl phosphate, 9 parts of red phosphorus, 0.5 parts of accelerator TMTD, 3 parts of DCP, and 1 part of HVA-2.
[0017] Among them, the enhancer includes sodium silicate, ferric chloride and aluminum hydroxide; the preparation process of the enhancer is: polyvinyl alcohol is melted at 262°C to form a polyvinyl alcohol melt, and then aluminum hydroxide with a particle size of 2 mm is put into the polyvinyl alcohol melt, and after mixing evenly, the excess polyvinyl alcohol melt on the surface is drained off, and then a mixture of ferric chloride and sodium silicate with a particle size of 0.1 mm (ferric chloride: sodium silicate (W / W) = 2:1) is mixed evenly with aluminum hydroxide, and then dried at 55°C for 10 minutes and passed through a 200-mesh sieve to obtain the enhancer.
[0018] The insulating layer includes 70 parts of cross-linked polypropylene, 15 parts of borax, 8 parts of magnesium hydroxide, 3 parts of ammonium polyphosphate and 1 part of dicyandiamide by weight. The preparation process is: firstly, the cross-linked polypropylene is melted at 170°C to form a cross-linked polypropylene melt, and then the borax, magnesium hydroxide, ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0019] A tear-resistant photovoltaic cable comprises a conductor, an insulating layer and a sheath layer, wherein the outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer, such as Figure 1 shown.
[0020] Example 2 The sheath material includes, by weight, 100 parts of ethylene propylene rubber, 10 parts of cross-linked polyethylene, 5 parts of zinc oxide, 2 parts of stearic acid, 1 part of paraffin, 2 parts of antioxidant RD, 10 parts of zinc borate, 200 parts of reinforcing agent, 10 parts of high wear-resistant furnace black, 10 parts of tricresyl phosphate, 10 parts of red phosphorus, 0.5 parts of accelerator TMTD, 3 parts of DCP, and 2 parts of HVA-2.
[0021] Among them, the enhancer includes sodium silicate, ferric chloride and aluminum hydroxide; the preparation process of the enhancer is: polyvinyl alcohol is melted at 264°C to form a polyvinyl alcohol melt, and then aluminum hydroxide with a particle size of 4 mm is put into the polyvinyl alcohol melt. After mixing evenly, the excess polyvinyl alcohol melt on the surface is drained off, and then a mixture of ferric chloride and sodium silicate with a particle size of 0.2 mm (ferric chloride: sodium silicate (W / W) = 3:2) is mixed evenly with aluminum hydroxide, and then dried at 60°C for 13 minutes and passed through a 200-mesh sieve to obtain the enhancer.
[0022] The insulating layer includes 90 parts of cross-linked polypropylene, 17 parts of borax, 8 parts of magnesium hydroxide, 4 parts of ammonium polyphosphate and 2 parts of dicyandiamide by weight. The preparation process is: firstly, the cross-linked polypropylene is melted at 174°C to form a cross-linked polypropylene melt, and then the borax, magnesium hydroxide, ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0023] A tear-resistant photovoltaic cable comprises a conductor, an insulating layer and a sheath layer, wherein the outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer, such as Figure 1 shown.
[0024] Example 3 The sheath material includes, by weight, 120 parts of ethylene propylene rubber, 13 parts of cross-linked polyethylene, 7 parts of zinc oxide, 4 parts of stearic acid, 2 parts of paraffin, 5 parts of antioxidant RD, 12 parts of zinc borate, 200 parts of reinforcing agent, 12 parts of high wear-resistant furnace black, 13 parts of tricresyl phosphate, 13 parts of red phosphorus, 1 part of accelerator TMTD, 5 parts of DCP, and 2 parts of HVA-2.
[0025] Among them, the enhancer includes sodium silicate, ferric chloride and aluminum hydroxide; the preparation process of the enhancer is: polyvinyl alcohol is melted at 267°C to form a polyvinyl alcohol melt, and then aluminum hydroxide with a particle size of 5 mm is put into the polyvinyl alcohol melt. After mixing evenly, the excess polyvinyl alcohol melt on the surface is drained off, and then a mixture of ferric chloride and sodium silicate with a particle size of 0.3 mm (ferric chloride: sodium silicate (W / W) = 4:3) is mixed evenly with aluminum hydroxide, and then dried at 65°C for 15 minutes and passed through a 200-mesh sieve to obtain the enhancer.
[0026] The insulating layer includes 100 parts of cross-linked polypropylene, 20 parts of borax, 10 parts of magnesium hydroxide, 5 parts of ammonium polyphosphate and 3 parts of dicyandiamide by weight. The preparation process is: firstly, the cross-linked polypropylene is melted at 176°C to form a cross-linked polypropylene melt, and then the borax, magnesium hydroxide, ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0027] A tear-resistant photovoltaic cable comprises a conductor, an insulating layer and a sheath layer, wherein the outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer, such as Figure 1 shown.
[0028] Comparative Example 1 The sheath material includes, by weight, 120 parts of ethylene propylene rubber, 13 parts of cross-linked polyethylene, 7 parts of zinc oxide, 4 parts of stearic acid, 2 parts of paraffin, 5 parts of antioxidant RD, 12 parts of zinc borate, 200 parts of aluminum hydroxide, 12 parts of high wear-resistant furnace black, 13 parts of tricresyl phosphate, 13 parts of red phosphorus, 1 part of accelerator TMTD, 5 parts of DCP, and 2 parts of HVA-2.
[0029] The insulating layer includes 100 parts of cross-linked polypropylene, 20 parts of borax, 10 parts of magnesium hydroxide, 5 parts of ammonium polyphosphate and 3 parts of dicyandiamide by weight. The preparation process is: firstly, the cross-linked polypropylene is melted at 176°C to form a cross-linked polypropylene melt, and then the borax, magnesium hydroxide, ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0030] A tear-resistant photovoltaic cable comprises a conductor, an insulating layer and a sheath layer. The outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer.
[0031] Comparative Example 2 The sheath material includes, by weight, 120 parts of ethylene propylene rubber, 13 parts of cross-linked polyethylene, 7 parts of zinc oxide, 4 parts of stearic acid, 2 parts of paraffin, 5 parts of antioxidant RD, 12 parts of zinc borate, 200 parts of reinforcing agent, 12 parts of high wear-resistant furnace black, 13 parts of tricresyl phosphate, 13 parts of red phosphorus, 1 part of accelerator TMTD, 5 parts of DCP, and 2 parts of HVA-2.
[0032] The reinforcing agent is a mixture of ferric chloride and sodium silicate (ferric chloride: sodium silicate (W / W) = 4:3).
[0033] The insulating layer includes 100 parts of cross-linked polypropylene, 20 parts of borax, 10 parts of magnesium hydroxide, 5 parts of ammonium polyphosphate and 3 parts of dicyandiamide by weight. The preparation process is: firstly, the cross-linked polypropylene is melted at 176°C to form a cross-linked polypropylene melt, and then the borax, magnesium hydroxide, ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0034] A tear-resistant photovoltaic cable comprises a conductor, an insulating layer and a sheath layer. The outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer.
[0035] Comparative Example 3 The sheath material includes, by weight, 120 parts of ethylene propylene rubber, 13 parts of cross-linked polyethylene, 7 parts of zinc oxide, 4 parts of stearic acid, 2 parts of paraffin, 5 parts of antioxidant RD, 12 parts of zinc borate, 200 parts of reinforcing agent, 12 parts of high wear-resistant furnace black, 13 parts of tricresyl phosphate, 13 parts of red phosphorus, 1 part of accelerator TMTD, 5 parts of DCP, and 2 parts of HVA-2.
[0036] Among them, the enhancer includes sodium silicate, ferric chloride and aluminum hydroxide; the preparation process of the enhancer is: polyvinyl alcohol is melted at 267°C to form a polyvinyl alcohol melt, and then aluminum hydroxide with a particle size of 5 mm is put into the polyvinyl alcohol melt. After mixing evenly, the excess polyvinyl alcohol melt on the surface is drained off, and then a mixture of ferric chloride and sodium silicate with a particle size of 0.3 mm (ferric chloride: sodium silicate (W / W) = 4:3) is mixed evenly with aluminum hydroxide, and then dried at 65°C for 15 minutes and passed through a 200-mesh sieve to obtain the enhancer.
[0037] The insulating layer includes 100 parts of cross-linked polypropylene, 5 parts of ammonium polyphosphate and 3 parts of dicyandiamide by weight. The preparation process is: firstly, the cross-linked polypropylene is melted at 176°C to form a cross-linked polypropylene melt, and then the ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0038] A tear-resistant photovoltaic cable comprises a conductor, an insulating layer and a sheath layer. The outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer.
[0039] Comparative Example 4 The sheath material includes, by weight, 120 parts of ethylene propylene rubber, 13 parts of cross-linked polyethylene, 7 parts of zinc oxide, 4 parts of stearic acid, 2 parts of paraffin, 5 parts of antioxidant RD, 12 parts of zinc borate, 200 parts of aluminum hydroxide, 12 parts of high wear-resistant furnace black, 13 parts of tricresyl phosphate, 13 parts of red phosphorus, 1 part of accelerator TMTD, 5 parts of DCP, and 2 parts of HVA-2.
[0040] The insulating layer includes 100 parts of cross-linked polypropylene, 5 parts of ammonium polyphosphate and 3 parts of dicyandiamide by weight. The preparation process is: firstly, the cross-linked polypropylene is melted at 176°C to form a cross-linked polypropylene melt, and then the ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0041] A tear-resistant photovoltaic cable comprises a conductor, an insulating layer and a sheath layer. The outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer.
[0042] Comparative Example 5 A tear-resistant photovoltaic cable comprises a conductor, an insulating layer and a cross-linked polyethylene sheath layer. The outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer.
[0043] The insulating layer includes 100 parts of cross-linked polypropylene, 5 parts of ammonium polyphosphate and 3 parts of dicyandiamide by weight. The preparation process is: firstly, the cross-linked polypropylene is melted at 176°C to form a cross-linked polypropylene melt, and then the ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
[0044] Cable performance test Tear strength test: The tear strength of the photovoltaic cables of the same specification prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to the GB / T 1040-2006 test standard. The test results are shown in Table 1.
[0045] Table 1 Tear strength of photovoltaic cables
[0046] A cutter was used to make the same number of and same size of damages on the sheath layer of the photovoltaic cables of the same specification prepared in Examples 1 to 3 and Comparative Examples 1 to 5, and after standing for 5 minutes, the tear strength of the photovoltaic cables prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to the GB / T 1040-2006 test standard. The test results are shown in Table 2.
[0047] Table 2 Tear strength of damaged photovoltaic cables
[0048] It can be seen from Tables 1 and 2 that the photovoltaic cable prepared by the present invention has good tear resistance, and even after the outer layer of the photovoltaic cable is damaged and subjected to external force, it can maintain good tear resistance, thereby avoiding tearing during use, which not only affects the integrity of the cable, but may also cause power transmission failures and even lead to safety accidents.
[0049] Flame retardant performance test: The flame retardant properties of the photovoltaic cables of the same specifications prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested according to the GB / T 19666 test standard. The self-extinguishing time and the coking height of the photovoltaic cables of the same specifications prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were recorded after the flame was removed under the condition of burning at 200°C for 15 minutes. The test results are shown in Table 3.
[0050] Table 3 Self-extinguishing time and coking height of photovoltaic cables
[0051] According to the GB / T 17651 test standard, the smoke generated by the burning of the photovoltaic cables of the same specifications prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was projected with light at 200°C, and the light transmittance of the smoke when the photovoltaic cables of the same specifications prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were burned was recorded. The test results are shown in Table 4.
[0052] Table 4 Photovoltaic cable smoke transmittance
[0053] It can be seen from Table 3 and Table 4 that the photovoltaic cable prepared in the present invention has good flame retardant properties, and can enable the photovoltaic cable to operate more stably in a high temperature environment.
[0054] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A solar photovoltaic cable sheath material, characterized in that: It includes the following components: ethylene propylene rubber, cross-linked polyethylene, zinc oxide, stearic acid, paraffin, antioxidant RD, zinc borate, reinforcing agent, high wear-resistant furnace black, tricresyl phosphate, red phosphorus, accelerator TMTD, DCP, HVA-2; Among them, the enhancer includes sodium silicate, ferric chloride and aluminum hydroxide; the preparation process of the enhancer is: melt polyvinyl alcohol to form a polyvinyl alcohol melt, then put aluminum hydroxide into the polyvinyl alcohol melt, mix them evenly, drain the excess polyvinyl alcohol melt on the surface, then mix the ferric chloride and sodium silicate mixture with aluminum hydroxide evenly, and then dry and filter to obtain the enhancer.
2. The solar photovoltaic cable sheath material according to claim 1, characterized in that: During the preparation of the reinforcing agent, the melting temperature of polyvinyl alcohol is 262~267℃.
3. The solar photovoltaic cable sheath material according to claim 1, characterized in that: During the preparation of the enhancer, the mixture of ferric chloride and sodium silicate is uniformly mixed with aluminum hydroxide and then dried at 55-65° C. for 10-15 minutes.
4. The solar photovoltaic cable sheath material according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 70-120 parts of ethylene-propylene rubber, 10-13 parts of cross-linked polyethylene, 3-7 parts of zinc oxide, 1-4 parts of stearic acid, 1-2 parts of paraffin, 2-5 parts of antioxidant RD, 8-12 parts of zinc borate, 150-200 parts of reinforcing agent, 10-12 parts of high wear-resistant furnace black, 9-13 parts of tricresyl phosphate, 9-13 parts of red phosphorus, 0.5-1 parts of accelerator TMTD, 3-5 parts of DCP and 1-2 parts of HVA-2.
5. The solar photovoltaic cable sheath material according to claim 4, characterized in that: Specifically, it includes the following components in parts by weight: 100 parts of ethylene propylene rubber, 10 parts of cross-linked polyethylene, 5 parts of zinc oxide, 2 parts of stearic acid, 1 part of paraffin, 2 parts of antioxidant RD, 10 parts of zinc borate, 200 parts of reinforcing agent, 10 parts of high wear-resistant furnace black, 10 parts of tricresyl phosphate, 10 parts of red phosphorus, 0.5 parts of accelerator TMTD, 3 parts of DCP, and 2 parts of HVA-2.
6. The solar photovoltaic cable sheath material according to claim 1, characterized in that: In the mixture of ferric chloride and sodium silicate, the weight ratio of ferric chloride to sodium silicate is 2-4:1-3.
7. The solar photovoltaic cable sheath material according to claim 1, characterized in that: The particle size of aluminum hydroxide is 2-5 mm, and the particle sizes of ferric chloride and sodium silicate are 0.1-0.3 mm; the mixture of ferric chloride and sodium silicate is evenly mixed with aluminum hydroxide and dried, and then filtered through a 200-mesh sieve.
8. A tear-resistant cable, comprising a conductor, an insulating layer and a sheath layer, wherein the outer side of the conductor is wrapped with the insulating layer, and the outer side of the insulating layer is wrapped with the sheath layer, characterized in that: The sheath layer is made of the sheath material according to any one of claims 1 to 6; the insulating layer comprises cross-linked polypropylene, borax, magnesium hydroxide, ammonium polyphosphate and dicyandiamide.
9. The tear-resistant cable according to claim 8, characterized in that The insulating layer specifically comprises the following components in parts by weight: 70-100 parts of cross-linked polypropylene, 15-20 parts of borax, 8-10 parts of magnesium hydroxide, 3-5 parts of ammonium polyphosphate and 1-3 parts of dicyandiamide.
10. The tear-resistant cable according to claim 9, characterized in that The preparation process of the insulating layer is as follows: first, the cross-linked polypropylene is melted at 170-176°C to form a cross-linked polypropylene melt, and then borax, magnesium hydroxide, ammonium polyphosphate and dicyandiamide are blended to form a blend, which is added to the cross-linked polypropylene melt, mixed evenly by mechanical blending, and then the blended material is coated on the outer layer of the conductor by an extrusion process to obtain the insulating layer.
Citation Information
Cited By
Anti-aging medium and low voltage polyvinyl chloride cable and production method thereof
CN120221182A
A kind of anti-aging medium and low voltage polyvinyl chloride cable and its production method
CN120221182B